2022
DOI: 10.3390/su142416571
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of TMT Experience Heterogeneity on Enterprise Innovation Quality: Empirical Analysis on Chinese Listed Companies

Abstract: High-quality innovation can solve the “bottleneck” problem of key enterprise technologies and drive the high-quality development of enterprises. Therefore, how to improve innovation quality has become a growing concern in the academic industry. In previous studies, the impact of TMT experience heterogeneity on enterprise innovation quality has not been well explored. Based on the panel data of Chinese A-share listed companies, this paper explored how TMT experience heterogeneity affects enterprise innovation q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Younger executives and older executives tend to differ in terms of management experience, risk preference, and information acquisition and processing [57][58][59]. As Hambrick and Mason (1984) have pointed out, age to some extent reflects an executive's experience and risk preference [39].…”
Section: The Moderating Effects Of Tmt Agementioning
confidence: 99%
See 1 more Smart Citation
“…Younger executives and older executives tend to differ in terms of management experience, risk preference, and information acquisition and processing [57][58][59]. As Hambrick and Mason (1984) have pointed out, age to some extent reflects an executive's experience and risk preference [39].…”
Section: The Moderating Effects Of Tmt Agementioning
confidence: 99%
“…To a certain extent, the characteristics of TMTs reflect their perceptions and values. Different TMT characteristics lead to differences in motivations such as maintaining reputation [57,94,95], risk aversion [96][97][98], and catching up with and imitating peers [99][100][101]. The current research mainly focuses on the mechanism of peer effects in corporate decisionmaking, such as information transmission [24], product market competition [24,41], and economic policy uncertainty [102] while less attention is paid to TMT characteristics.…”
Section: Further Analysis 451 the Impact Of Digital Transformation On...mentioning
confidence: 99%
“…Drawing on the upper echelons theory, we investigated how TMT power moderated the relationship between DSC and sustainable TC provision, which contributed to the advancement of supply chain management theory and TC theory [39]. Some studies suggested that enterprises decision-making was a process of negotiation and compromise among TMT, shareholders and employees, and that the characteristics of TMT would have a significant influence on enterprises decisions [45]. The development and execution of DSC strategy is the outcome of effective interactions and collaboration among TMT members, while TC provision is a major financial decision for the enterprise.…”
Section: The Moderating Effect Of Tmt_powermentioning
confidence: 99%
“…Second, we broadened the application domain of the upper echelon theory [44]. The extant literature highlighted the role of TMT in supply chain management [45], but its overlooked the power of TMT. We elucidated the effect of TMT power on the relationship between DSC and TC provision and offered a foundation for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that the heterogeneity of the TMT is conducive to bringing more information and diversified cognition to the enterprise, so as to improve business performance. Ma et al (2022) tested the impact of TMT experience heterogeneity on enterprise innovation quality, and found that TMT functional experience heterogeneity positively affects partner diversity to promote innovation quality. Tao (2018) took science and technology 1 Zhongnan University of Economics and Law, Wuhan, China 2 Jiangxi University of Finance and Economics, Nanchang, China 3 Auckland University of Technology, Auckland, New Zealand enterprises as the research object and found that the diversity of the TMT's characteristics were positively correlated with corporate performance, that is, increasing the proportion of female leaders could improve corporate performance.…”
Section: Introductionmentioning
confidence: 99%